Observing English classroom in the digital era - Susanto, Budi; Wajdi, Majid; Sariono, Agus; Sudarmaningtyas, Anastasia Erna Rochiyati (Journal of Language and Pragmatics Studies, 2022)
Teaching and learning English for millennials requires a different  approach from previous generations unfamiliar with digital technology advances.  This paper tries to discuss and see how English teachers insert digital technology (WHAT) into the classroom learning process. To obtain the data for this study, the researchers observed a teacher (HOW) inserting digital technology into learning. The researchers used recording techniques (audio and video) and field notes to complement the observation technique. The observations show that the teacher applies the active student learning method by applying the principle of time distribution for students and teachers. The teacher only uses up to 15% of the available time allocation, and students have more than 85% of the time to do and practice the points on the learning material. Students get extensive opportunities to experience learning with the aim that they will gain and be able to improve 1) their digital skill; 2) the growth and improvement of the students' self-confidence and other soft skills. The students' Youtube content.